Technology Today and Tomorrow - Student Workbook - A. Brusic Sharon (MC Graw Hill, 1998)
Technology: Today and Tomorrow uses a systems-based, problem-solving approach to teaching technology. The text addresses all aspects of technology and includes science and mathematics connections. Fascinating facts, hands-on activities and career choices in technology will keep your students' interest.